Exploring the role of a glycosylated L-asparaginase expressed by a recombinant Pichia pastoris as an antileukemic biopharmaceutical - Kleingesinds, Eduardo Krebs (2021)
According to the World Health Organization (WHO), in 2020, 474 519 new cases of leukemia were reported around the world, and 311 594 new deaths were reported. The importance of L-asparaginase (LASNase) as a biopharmaceutical to treat Acute Lymphoblastic Leukemia (ALL) is recognized worldwide. This work describes the bioprocessing of L-ASNase from Erwinia chrysanthemi expressed extracellularly by Pichia pastoris with a human-like glycosylation pattern. Firstly, it was optimized the upstream conditions in the orbital shaker flask. Then, it was scaled up using a 3L benchtop bioreactor at batch mode under 35 °C and 1.5% methanol as an inductor for L-ASNase production. The downstream processing was evaluated using crossflow ultrafiltration with different cut-offs (10-100 kDa) followed by cation exchange chromatography and size exclusion chromatography. It was possible to reach a final yield of 54.93% with a purification factor of 70.93 fold and the proteomics data confirmed the attainment of an extremely pure enzyme. At pH 8.0 and 50 °C, the enzyme showed its optimum activity. Kinetic parameters, kM and Vmax, were found to be 76.4 µM and 0.065 µmol min-1, respectively. The thermodynamic study showed that the enzyme irreversible deactivation is well described by first-order kinetics. Finally, using a high throughput fluorescentbased in vitro experimental platform, it was investigated the concomitant impact of this recombinant L-ASNase on enhanced green fluorescent protein (eGFP)-labeled tumor cell lines (SEMK2, HB119, REH, and MV411) when co-cultured with the mCherry-labelled bone marrow fibroblastic stroma cells HS5. The outcomes of this research suggest that the eGFP-Hb11-9 strain was the most sensitive strain when treated with the glycosylated L-ASNase, in contrast with the eGFP-REH that was the most resistant linage. It was also observed lower effectiveness of the drug when tumor cells were co-cultured with stromal cells than when tumor cells were cultured on their own. Hence, this work paves the way for production, scale-up, and pre-clinical trials of this promising novel biopharmaceutical, which may help improve the remission rates and quality of life for many cancer patients around the world.